2003
DOI: 10.1172/jci200317991
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus anthracis lethal toxin induces TNF-α–independent hypoxia-mediated toxicity in mice

Abstract: Bacillus anthracis lethal toxin (LT) is the major virulence factor of anthrax and reproduces most of the laboratory manifestations of the disease in animals. We studied LT toxicity in BALB/cJ and C57BL/6J mice. BALB/cJ mice became terminally ill earlier and with higher frequency than C57BL/6J mice. Timed histopathological analysis identified bone marrow, spleen, and liver as major affected organs in both mouse strains. LT induced extensive hypoxia. Crisis was due to extensive liver necrosis accompanied by pleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
70
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(76 citation statements)
references
References 54 publications
6
70
0
Order By: Relevance
“…One major feature observed on autopsy is extensive haemorrhaging of the lymphoid organs (such as the lymph nodes and spleen) (Guarner et al, 2003). Studies in a mouse model have shown that LT injection induces thrombopenia (Moayeri et al, 2003), associated with a slower clotting time, a decrease in fibrinogenaemia and the accumulation of fibrin deposits in tissue sections (Culley et al, 2005). These autopsy findings are consistent with recent reports showing that LT and ET extensively disrupt platelet function and aggregation (Kau et al, 2005;Alam et al, 2006).…”
Section: The Terminal Phase: Vascular Collapse Provoked By the Massivsupporting
confidence: 82%
“…One major feature observed on autopsy is extensive haemorrhaging of the lymphoid organs (such as the lymph nodes and spleen) (Guarner et al, 2003). Studies in a mouse model have shown that LT injection induces thrombopenia (Moayeri et al, 2003), associated with a slower clotting time, a decrease in fibrinogenaemia and the accumulation of fibrin deposits in tissue sections (Culley et al, 2005). These autopsy findings are consistent with recent reports showing that LT and ET extensively disrupt platelet function and aggregation (Kau et al, 2005;Alam et al, 2006).…”
Section: The Terminal Phase: Vascular Collapse Provoked By the Massivsupporting
confidence: 82%
“…Circulating monocyte levels were also unaffected in LT-treated rats, although measurements were taken only 3 h and 9 h after administration (Cui et al, 2004). In LT-treated mice, however, a rapid depletion of monocytes was observed, but the cause of this depletion was not investigated (Moayeri et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Evasion of the host innate immune response by triggering macrophage cell death is a common strategy used by a number of bacterial pathogens including Shigella, Salmonella and Yersinia (Navarre and Zychlinsky, 2000). Although LT-induced death of macrophages does not appear to play a role in how animals die of anthrax (Moayeri et al, 2003;Cui et al, 2004), it may be a strategy used by B. anthracis to establish an infection. Our results indicate that LT-induced death of a human monocytic cell line depends on its differentiation state and occurs through a mechanism that is distinct from those that occur in mouse macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The β test described here by Amberg et al (7) further highlights the unique, localized Ca 2+ signaling mechanism in vascular myocytes and the role of the β subunit in tuning the Ca 2+ sensitivity of the BK channel complex. Functional changes in coupling between the SR and the sarcolemma, resulting from the altered expression of BK β subunits, may be a key mechanism underlying variations in vascular tone in vivo.…”
mentioning
confidence: 69%